Is Recurving an Effective Strategy of Trifolium repens L. to Augment Reproduction? - Mustaqeem Ahmad; Sanjay Kr. Uniyal (Scientifica)
Flowers of Trifolium repens L. show recurving. We, therefore, studied whether this is an effective strategy employed by the species to augment reproduction. For this, fifty plants of the species were tagged and monitored. This included twenty control and twenty constrained to recurve. The remaining 10 plants were covered with a net to limit cross-pollination. Daily observations on the plants were recorded. No significant difference in the number of flowers per inflorescence between control and constrained plants was found. However, a significant difference (p<0.001) in the number of seeds produced by control (68.35±3.92) and constrained plants (22.25 ± 1.35) was observed. Three times more seeds, without compromising on seed mass (p>0.05), were produced in the control plants. No seeds were produced in the flowers that were netted. Thus, recurving appears to help T. repens in reproduction.